FINANCIAL DISTRESS ANALYSIS WITH ALTMAN Z-SCORE METHOD: FINANCIAL DISTRESS ANALYSIS WITH ALTMAN Z-SCORE METHOD - Deti Susilawati; Sembiring, Evi Dora; Pertiwi, Sari Putri; Nurul Afifah, Panisya; Shavab, Firli (PT Larva Wijaya Penerbit, 2024)
This research aims to determine bankruptcy predictions and determine the average value of financial ratios used as Altman Z-Score analysis for metal and mineral industrial companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2021 period. The population in this study is Metal and Mineral Industrial Companies listed on the Indonesia Stock Exchange during the 2020-2021 period with a total of 7 companies using annual financial report data taken by purposive sampling, resulting in a sample of 14 data that meets the criteria. The sampling criteria selected were 1) Metal and mineral industrial companies listed on the Indonesia Stock Exchange (BEI) which have gone public and are listed on the BEI during the 2020-2021 period. 2) Companies report financial statements in rupiah units. 3) The financial report contains information related to all variables studied in 2020-2021. The analysis method used is the Altman Z-Score method analysis where there are 2 (two) research periods, namely 2020-2021. The results of this research show that: in 2020, there were 5 (companies) in the safe zone category, one company in the gray zone category, and one company in the distress zone category. The company in the safe zone category is PT. Aneka Tambang Tbk, PT. Citra Mineral Investindo Tbk, PT. PAM Mineral Tbk, PT. Kapuas Prima Coal Tbk, and PT. Central Omega Resources Tbk. Companies in the gray zone category are PT. Iifshdeco Tbk. The company in the distress zone category is PT. Timah Tbk. In 2021, the seven companies, namely PT. Aneka Tambang Tbk, PT. Citra Mineral Investindo Tbk, PT. Timah Tbk, PT. PAM Mineral Tbk, PT. Kapuas Prima Coal Tbk, PT. Central Omega Resources Tbk, and PT. Iifshdeco Tbk is in the safe zone category.